2004
DOI: 10.2337/diabetes.53.2.294
|View full text |Cite
|
Sign up to set email alerts
|

Strength Training Increases Insulin-Mediated Glucose Uptake, GLUT4 Content, and Insulin Signaling in Skeletal Muscle in Patients With Type 2 Diabetes

Abstract: Strength training represents an alternative to endurance training for patients with type 2 diabetes. Little is known about the effect on insulin action and key proteins in skeletal muscle, and the necessary volume of strength training is unknown. A total of 10 type 2 diabetic subjects and 7 healthy men (control subjects) strength-trained one leg three times per week for 6 weeks while the other leg remained untrained. Each session lasted no more than 30 min. After strength training, muscle biopsies were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

26
318
9
12

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 495 publications
(365 citation statements)
references
References 53 publications
26
318
9
12
Order By: Relevance
“…Physical inactivity or muscle disuse is linked to the development of insulin resistance and type 2 diabetes [12,13], whereas exercise training can reduce insulin resistance [14,15]. The present findings of a marked difference in limb palmitate kinetics between arm and leg might be interpreted from the perspective of a different activity pattern between the two extremities.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Physical inactivity or muscle disuse is linked to the development of insulin resistance and type 2 diabetes [12,13], whereas exercise training can reduce insulin resistance [14,15]. The present findings of a marked difference in limb palmitate kinetics between arm and leg might be interpreted from the perspective of a different activity pattern between the two extremities.…”
Section: Discussionmentioning
confidence: 63%
“…Physical inactivity or muscle disuse is recognised as one of the risk factors for the development of insulin resistance and type 2 diabetes [12,13]. Against this, it has been shown that exercise training can reduce insulin resistance in the leg of diabetic patients [14,15]. Recently, evidence has been presented for heterogeneity towards lipolysis in human skeletal muscles [16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous resistance-type exercise intervention studies in uncomplicated T2D patients have applied higher-intensity exercise and reported strength increases between 25 and 75% (29,(56)(57)(58)(59)(60). Some of these intervention studies report significant improvements in HbA 1c (56,57), and glucose area under the curve (58,61).…”
Section: Discussionmentioning
confidence: 99%
“…Resistance training in particular has been seen to improve both muscle strength and 20 mass as well as insulin sensitivity (Brooks et al, 2007;Cauza et al, 2005;Dunstan et 21 al., 2002;Holten et al, 2004;LeBrasseur et al, 2011;Mann et al, 2014). For these 22 reasons, it may be desirable that type 2 diabetes patients would begin an appropriate 23 exercise training program as soon as possible after diagnosis to prevent, or at least 24 limit, the decline in neuromuscular function.…”
Section: Introductionmentioning
confidence: 99%